EVALUATION OF NUTRIENT FACTORS AND PROCESS PARAMETERS INFLUENCE ON BACTERIOCIN PRODUCTION BY LACTOBACILLUS ACIDOPHILUS SK 01 STRAIN - V.RAMESH KUMAR; S.KARTHICK RAJA NAMASIVAYAM; S.CHANDRA MOHAN; SRIMANTI DEBNATH (International Journal of Pharma and Bio Sciences, 2015)
Bacteriocin is the anti microbial peptide produced by lactic acid bacteria and extensively used as food preservative in the various parts of the world. Production of bacteriocin is influenced by various parameters including nutrient factors supplied from the media and the process parameters. In the present study, effect of nutrient factors and process parameters on bacteriocin production by Lactobacillus acidophilus SK 01 strain isolated from milk samples has been discussed. Optimization study was carried out by changing various carbon and nitrogen sources, process parameters such as duration of incubation period, pH and temperature. Maximum bacteriocin production was observed during 42th hour to 60th hours of incubation glucose, ammonium nitrate and urea as the carbon, nitrogen sources. The present study would suggests the optimization of media and process parameters for the bacteriocin production by lactic acid bacteria leads to development of novel safe food preservative against food spoilage organisms.